A Vlogging as a Media in Teaching Speaking Descriptive Text for Junior High - Christiandari, Ayu Arivian (RETAIN : Journal of Research in English Language Teaching, 2022)
echnology and social media are an excellent additionto the English learning process since they provideopportunities for students to develop their English-speakingabilities.Avlog is one of the many mediums that may beutilized to help. The background of this study is since in the academic year 2019/2020, 36 students from one of thePublic Junior High Schools in Sidoarjo, who need to strengthen their speaking skills.Some of themdidn't know how toproperly present their views.This study aims to learn about: (a) the use of vlogging as a learning medium for Junior High students in speaking Descriptive Text, (b) the performance of students who use vlog as a learning medium in speaking Descriptive Text, and (c) the students' reactions to using vlog as a learning medium in speaking Descriptive Text. This research is implemented a qualitative and Descriptive research Design. Interview and Students’ vlog were the instruments that were applied in this research. The researcher analyzed the data using 3 steps, they are assemblingthedata,codingthedata,andcomparingthedata.Ineachstep,theresearcherneedsStudents’andteachers’participation to complete the data. The researcher found that Vlogging can be positively used in teaching Descriptive Text, especially in speaking skill. The implementation of Vlog strongly affects them. It is hoped that boosting Vlog with smart vlogging stages and  scoring reflection as feedback would enhance students' English-speaking abilities